Reproductive status of Onchocerca volvulus after ivermectin treatment in an ivermectin-naïve and a frequently treated population from Cameroon. - Hugues C Nana-Djeunga; Catherine Bourguinat; Sébastien D Pion; Jean Bopda; Jonas A Kengne-Ouafo; Flobert Njiokou; Roger K Prichard; Samuel Wanji; Joseph Kamgno; Michel Boussinesq (Public Library of Science (PLoS), 2014)
For two decades, onchocerciasis control has been based on mass treatment with ivermectin (IVM), repeated annually or six-monthly. This drug kills Onchocerca volvulus microfilariae (mf) present in the skin and the eyes (microfilaricidal effect) and prevents for 3-4 months the release of new mf by adult female worms (embryostatic effect). In some Ghanaian communities, the long-term use of IVM was associated with a more rapid than expected skin repopulation by mf after treatment. Here, we assessed whether the embryostatic effect of IVM on O. volvulus has been altered following frequent treatment in Cameroonian patients.Onchocercal nodules were surgically removed just before (D0) and 80 days (D80) after a standard dose of IVM in two cohorts with different treatment histories: a group who had received repeated doses of IVM over 13 years, and a control group with no history of large-scale treatments. Excised nodules were digested with collagenase to isolate adult worms. Embryograms were prepared with females for the evaluation of their reproductive capacities.Oocyte production was not affected by IVM. The mean number of intermediate embryos (morulae and coiled mf) decreased similarly in the two groups between D0 and D80. In contrast, an accumulation of stretched mf, either viable or degenerating, was observed at D80. However, it was observed that the increase in number of degenerating mf between D0 and D80 was much lower in the frequently treated group than in the control one (Incidence Rate Ratio: 0.25; 95% CI: 0.10-0.63; p = 0.003), which may indicate a reduced sequestration of mf in the worms from the frequently treated group.IVM still had an embryostatic effect on O. volvulus, but the effect was reduced in the frequently treated cohort compared with the control population.